Snow cover maps (C1) of Guadalfeo Monitoring Network (Sierra Nevada, Spain) - María José Polo; Javier Herrero; Rafael Pimentel; María José Pérez-Palazón (PANGAEA, 2019)
This work presents the Guadalfeo Monitoring Network in Sierra Nevada (Spain), a snow monitoring network in the Guadalfeo Experimental Catchment, a semiarid area in southern Europe representative of snow packs with highly variable dynamics on both the annual and seasonal scales, and significant topographic gradients. The network includes weather stations that cover the high mountain area in the catchment and time-lapse cameras to capture the variability of the ablation phases on different spatial scales. This dataset consists of snow cover maps of the time-lapse camera C1 of the Guadalfeo Monitoring Network, at 10m x 10m spatial resolution and for those days when Landsat satellites overpasses the area (Pimentel et al., 2017).
Supplement to: Polo, MJ et al. (2019): The Guadalfeo Monitoring Network (Sierra Nevada, Spain): 14 years of measurements to understand the complexity of snow dynamics in semiarid regions. Earth System Science Data, 11(1), 393-407, https://doi.org/10.5194/essd-11-393-2019